Silymarin Protects Mouse Liver and Kidney from Thioacetamide Induced Toxicity by Scavenging Reactive Oxygen Species and Activating PI3K-Akt Pathway - Ghosh, Shatadal; Sarkar, Abhijit; Bhattacharyya, Sudip; Sil, Parames C. (Frontiers in Pharmacology, 2016)
Abstract: Silymarin (SMN) has been shown to possess a wide range of biological and pharmacological effects. Besides, SMN has antioxidant and free radical scavenging activities. Thioacetamide (TAA) is a well-documented liver toxin that requires oxidative bioactivation to elicit its hepatotoxic effect which ultimately modifies amine-lipids and proteins. Our study has been designed in a TAA exposed mouse model to investigate whether silymarin could protect TAA-induced oxidative stress mediated hepatic and renal damage. Results suggest that TAA generated reactive oxygen species (ROS), caused oxidative stress and induced apoptosis in the liver and kidney cells via JNK as well as PKC and MAPKs signalling. All these detrimental effects of TAA could, however, be suppressed by SMN which not only scavenged ROS but also induced PI3K-Akt cell survival pathway in the liver and prevented apoptotic pathways in both the organs. Histological studies, collagen staining and DNA fragmentation analysis also supported our results. Combining, we say that SMN possess beneficial role against TAA mediated hepatic and renal pathophysiology.